Pelatihan Integrasi Deep learning, Flipped classroom, dan STEAM untuk Guru Sekolah Dasar - Akmal, Atika Ulya; Kenedi, Ary Kiswanto; Muthie, Imam; Novariza, Rika; Mardin, Asna (Universitas Pahlawan Tuanku Tambusai, 2025)
This activity aimed to enhance elementary school teachers’ capacity in designing and implementing deep learning integrated with flipped classroom and STEAM approaches. The training was motivated by the limited understanding and skills among teachers to apply innovative learning aligned with the National Curriculum. The community service method included training, lesson planning workshops, classroom simulations, and on-site mentoring. Results showed a 56.9% increase in teacher understanding, along with the successful production of project-based lesson plans, digital learning media, and practical use of technology in flipped classrooms. Moreover, this activity fostered a reflective teacher community capable of sustaining interdisciplinary learning practices. The findings confirm that integrative training can effectively support learning transformation at the elementary level.